IMPLEMENTASI MANAJEMEN KEUANGAN DALAM MENINGKATKAN EFEKTIVITAS LAYANAN ADMINISTRASI DI PONDOK PESANTREN NURUL HIDAYAH AL-AMIN - Khasanudin, Ibnu; Khomsinnudin; Muntoha, Tohir (As-Sulthan Journal of Education, 2025)
This research was motivated by the problem of limited human resources in financial management and the low discipline of santri guardians in payments at Pondok Pesantren Nurul Hidayah Al-Amin, even though this boarding school is one of the best in West Tulang Bawang Regency. The purpose of the study was to examine the implementation of financial management, supporting factors, and obstacles in improving the effectiveness of administrative services. The research used a qualitative approach with a case study, and data collection techniques through observation, interviews, and documentation. The results showed that the implemented financial management runs optimally, although there are obstacles such as the low discipline of the santri guardians and the lack of experts. This problem can be overcome by planning, organizing, monitoring, and implementing a more transparent and efficient website-based payment system. In conclusion, good financial management and information technology support can increase the effectiveness of administrative services in Islamic boarding schools.